A Genome-wide View of Transcriptome Dynamics During Early Spike Development in Bread Wheat. Issue 1 (December 2018) - Li, Yongpeng; Fu, Xing; Zhao, Meicheng; Zhang, Wei; Li, Bo; An, Diaoguo; Li, Junming; Zhang, Aimin; Liu, Renyi; Liu, Xigang
Abstract Wheat spike development is a coordinated process of cell proliferation and differentiation with distinctive phases and architecture changes. However, the dynamic alteration of gene expression in this process remains enigmatic. Here, we characterized and dissected bread wheat spike into six developmental stages, and used genome-wide gene expression profiling, to investigate the underlying regulatory mechanisms. High gene expression correlations between any two given stages indicated that wheat early spike development is controlled by a small subset of genes. Throughout, auxin signaling increased, while cytokinin signaling decreased. Besides, many genes associated with stress responses highly expressed during the double ridge stage. Among the differentially expressed genes (DEGs), were identified 375 transcription factor (TF) genes, of which some homologs in rice orArabidopsis are proposed to function in meristem maintenance, flowering time, meristem initiation or transition, floral organ development or response to stress. Gene expression profiling demonstrated that these genes had either similar or distinct expression pattern in wheat. Several genes regulating spike development were expressed in the early spike, of whichEarliness per se 3 (Eps-3 ) was found might function in the initiation of spikelet meristem. Our study helps uncover important genes associated with apical meristem morphology and development in wheat.